If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 3n + 7 = 3 Reorder the terms: 5 + 7 + 3n = 3 Combine like terms: 5 + 7 = 12 12 + 3n = 3 Solving 12 + 3n = 3 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 3n = 3 + -12 Combine like terms: 12 + -12 = 0 0 + 3n = 3 + -12 3n = 3 + -12 Combine like terms: 3 + -12 = -9 3n = -9 Divide each side by '3'. n = -3 Simplifying n = -3
| 4(x-3)=6x+5-3x | | 6(J+3)=102 | | -6m-5(1+3m)=163 | | x+120=24-5x | | 2b+3c=57 | | 15=-4v-v | | -(3n-8)+2=-5(n-3)-(5-4n) | | (6-5)-(2*3-9)+2= | | -31+x=38+4x | | s=7(3.14)zh+2(3.14)z^2 | | 784=800-4x^2 | | 32^(1/8)*(n^11*m^7)^1/8 | | 4a-7(1-8a)=-127 | | x-5/3+1/9=7/9 | | 5y+7=-4+3y | | 5(n-2)-14n=-3n-(5+-4n) | | 6y-1o=49-17 | | 1/4(4x-8)-6=1/5(5x-10)-6 | | 30=-5d+5 | | 8=h/3 | | 8v-17-2v=13 | | 1/2x-13=8 | | 15+3n+8=-4 | | M+46=62 | | 0=8x+2x | | 18*x-2*y=26 | | 12x+7=-6+25 | | 3/8x=-6/5 | | 2x+40+4x-10+5x+55=360 | | 9an=6a(n-1)*3-9a(n-2)-18 | | Q=m-n/3p | | -6=4x+12 |